Postnatal diagnosis of an occult uterine scar dehiscence after three uncomplicated vaginal births after Caesarean section: A case report - Fong Lien Kwong; Ibraheem Hamoodi (Case Reports in Women's Health, 2020)
Introduction: The incidence of Caesarean sections has been increasing in the United Kingdom. Obstetricians have become more inclined to offer a trial of a vaginal birth to women following a single uncomplicated Caesarean section due to growing recognition of the high morbidity associated with repeat abdominal surgeries, and the relative rarity of a Caesarean scar defect causing complications at subsequent vaginal deliveries. The diagnosis of a Caesarean scar defect such as a uterine scar dehiscence in the postnatal period still remains elusive due to its vague presentation. An incorrect diagnosis or a delay in diagnosis can lead to unnecessary interventions or delay the management of patient symptoms. Case Presentation: A 35-year-old woman with a single Caesarean section and three subsequent uncomplicated vaginal deliveries was diagnosed with an occult scar dehiscence two weeks postnatally. She initially complained of persistent vaginal bleeding and underwent a suction evacuation for suspected retained placental tissue. Her symptoms did not improve, and a CT scan was requested to rule out a uterine perforation following the surgical procedure. The CT scan suggested a uterine dehiscence at the level of the previous scar. As the patient remained clinically well, her symptoms were managed conservatively. She underwent a laparoscopic sterilisation six months later and was discharged as the scar defect had fully resolved. Conclusion: Clinicians should remain vigilant about the possibility of an occult scar defect in women with a previous Caesarean section who present with persistent vaginal bleeding and pain in the postnatal period.